Ecological Mechanisms Underpinning Ecosystem Service Bundles in Marine Environments – A Case Study for Shellfish - Rullens, Vera; Lohrer, Andrew M.; Townsend, Michael; Pilditch, Conrad A. (Frontiers in Marine Science, 2019)
The supply of ecosystem services (ES) that benefit humanity are derived from multiple, interacting ecological functions and processes. Focusing on the ecological mechanisms that underpin ES delivery allows bundles of services to be identified, bridging a critical gap with management. Work in marine systems has not yet progressed to the identification of ES bundles, as a result of data scarcity and complications arising from system complexity and connectivity, as opposed to terrestrial systems where ES bundles have been more widely applied based on spatial clustering. To demonstrate the approach, identification of ES bundles provided by shellfish is used as a case-study. Shellfish provide a number of known ES that need to be strategically managed to ensure sustainable use. As a result of global degradations in shellfish beds ES have been lost, and restoration efforts emphasize the importance in regaining these services. A literature review, including 146 papers aimed specifically at linking shellfish to either ecosystem functions or ecosystem services, was conducted to establish key linkages between processes, functions and services. Based on co-occurrence of services and shared linkages, four bundles of services are identified, including Marine resources, Coastal health and quality, Habitat modification, and Biological structuring. Our study emphasizes the underpinning ecological mechanisms and the importance of interactions between services, expressed in the formation of bundles by mutual drivers and processes, as well as between services in different bundles, as either synergies or trade-offs. The approach enables the translation of ecological knowledge and creates generality to inform policy making and management, thereby providing a format useful for ecologists, managers and other stakeholders.